Pregnancy Outcomes According to Dialysis Commencing Before or After Conception in Women with ESRD - Jesudason, Shilpanjali (American Society of Nephrology, 2014)
BACKGROUND AND OBJECTIVES: Pregnancy in ESRD is rare and poses substantial risk for mother and baby. This study describes a large series of pregnancies in women undergoing long-term dialysis treatment and reviews maternal and fetal outcomes. Specifically, women who had conceived before and after starting long-term dialysis are compared. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENT: All pregnancies reported to the Australian and New Zealand Dialysis and Transplantation Registry from 2001 to 2011 (n=77), following the introduction of specific parenthood data collection, were analyzed. RESULTS: Between 2001 and 2011, there were 77 pregnancies among 73 women. Of these, 53 pregnancies were in women who conceived after long-term dialysis was established and 24 pregnancies occurred before dialysis began. The overall live birth rate (after exclusion of elective terminations) was 73%. In pregnancies reaching 20 weeks gestation, the live birth rate was 82%. Women who conceived before dialysis commenced had significantly higher live birth rates (91% versus 63%; P=0.03), but infants had similar birthweight and gestational age. This difference in live birth rate was primarily due to higher rates of early pregnancy loss before 20 weeks in women who conceived after dialysis was established. In pregnancies that reached 20 weeks or more, the live birth rate was higher in women with conception before dialysis commenced (91% versus 76%; P=0.28). Overall, the median gestational age was 33.8 weeks (interquartile range, 30.6–37.6 weeks) and median birthweight was 1750 g (interquartile range, 1130–2417 g). More than 40% of pregnancies reached >34 weeks’ gestation; prematurity at <28 weeks was 11.4% and 28-day neonatal survival rate was 98%. CONCLUSIONS: Women with kidney disease who start long-term dialysis after conception have superior live birth rates compared with those already established on dialysis at the time of conception, although these pregnancies remain high risk.